SIMULASI JARINGAN IEEE 802.11AX WIFI 6 MENGGUNAKAN SIMULATOR NS-3 UNTUK PENGUKURAN THROUGHPUT PADA BAND FREKUENSI 6 GHZ - Yeheskiel Mandala Putra; Theophilus Wellem (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The current generation WiFi technology, WiFi 6/6E, is based on the IEEE 802.11ax standard. The IEEE 802.11ax standard introduces several new features that make WiFi 6 superior to its predecessors, for example, 1024-QAM modulation and 6 GHz frequency band for WiFi 6E. This study aims to study the IEEE 802.11ax WiFi 6 standard, simulate an IEEE 802.11ax WiFi 6 network, and observe the throughput achieved in the 6 GHz frequency band using various payload sizes. The simulation is carried out using ns-3, a network simulator for various network models such as Ethernet, WiFi, and 4G LTE. The network topology used in the simulation consists of an access point (AP) and a client station (STA). The simulation results show that payload size significantly affects the network throughput. Simulations with a payload size of 64 and 1500 bytes, at a channel bandwidth (CBW) of 160 MHz and a guard interval (GI) of 800 ns, produce a throughput of 51 Mbps and 766.536 Mbps, respectively.